2007
DOI: 10.2174/187221007779814763
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Inorganic Solar Cells Using Quantum Structures

Abstract: Thermalization of photogenerated carriers in bulk materials is the main bottleneck for the conversion efficiency of conventional inorganic solar cells. Furthermore, despite extensive research, the achieved conversion efficiency is nearly saturated during the last decade. Therefore, new device concepts to break through the efficiency barrier are highly requested. Nanotechnologies are the building blocks for next-generation solar cells, because low-dimensional quantum structures can possibly reduce thermalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The author have developed hydrogenated protocrystalline Si (pc-Si:H) multilayer absorbers [18]. The pc-Si:H material is a highly H 2 -diluted a-Si:H material existing just [19]. The i-pc-Si:H multilayers exhibit a fast light-induced metastability with a low degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The author have developed hydrogenated protocrystalline Si (pc-Si:H) multilayer absorbers [18]. The pc-Si:H material is a highly H 2 -diluted a-Si:H material existing just [19]. The i-pc-Si:H multilayers exhibit a fast light-induced metastability with a low degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The pc-Si:H multilayer cell exhibits the rapider recovery than the undiluted a-Si:H cell. From the fast metastability and annealing behaviors of pc-Si:H multilayer solar cells, the vertically regular distribution of the isolated nc-Si grains [21] and the improved medium-range-order in the a-Si:H matrix [23] are considered to localize the photocreation near the grain boundary regions [19], and thereby suppress the photocreation of slow metastable defects in the pc-Si:H multilayers. From the visible photoluminescence (PL) peak measured at room temperature, the isolated nc-Si grains tend to act as radiative recombination centers of captured carriers, which may contribute to the good stability [14].…”
Section: Resultsmentioning
confidence: 99%
“…In QDSSCs dye is replaced by quantum dot. Quantum dot has tunable band gap properties, absorbs light up to IR region and produce multiple electrons to enhance efficiency of solar [14,[106][107][108][109] cells. In recent years it is reported that quantum dots (QDs) of InAs with 5, 10 and 12 nm size have 1.071, 0.553 and 0.045 eV band gap respectively.…”
Section: Materials For Qdsscsmentioning
confidence: 99%
“…From then on, the use of the multi-layered photovoltaic (MLPV) cells became one of the most used approaches for a high efficiency PV cell. Generally, such cells are p-i-n type diodes, with the intrinsic region formed by a multilayered structure [3][4][5][6][7][8][9][10][11][12][13][14][15]. Most of these cells have layers of tens or even hundreds of nanometer thickness, so that the quantum effects are reduced; nevertheless they are also called in some texts "quantum well" PV cells (see for instance Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The MLPV (and the multi-layered quantum well photovoltaic -MLQWPV) cells are 2D. In literature, they are divided in multiple quantum wells (MQW) and superlattice (SL) systems [5,14], the difference being based on the barrier layer thickness [14]. However, this interpretation is not correct.…”
Section: Introductionmentioning
confidence: 99%